Plan de negocios para la creación de la empresa Encanto Luminoso. (2024)
ext, a detailed analysis is presented for the development of a model of business focused on the production and marketing of artisanal candles under the brand Luminous Charm. This document addresses the background that underlies the need for sustainable and personalized candles in the market until the identification of the target market and the characteristics of the competition.